Space, time and irreversibility : The philosophical problems of contemporary astrophysics - Romero, Gustavo Esteban (2017)
Scientific philosophy is that which is informed by science. It uses exact tools such as logic and mathematics and provides a framework for scientific activity to solve more general questions about nature, the language we use to describe it, and the knowledge we obtain thanks to it. Many of the scientific philosophy theories can be proven and evaluated using scientific evidence. In this paper, I focus on showing how several classical philosophy topics, such as the nature of space and time or the dimensionality of the future, can be addressed philosophically using the tools from current astrophysics research and, in particular, from the study of black holes and gravitational waves.